Avaliação toxicológica do efluente de uma indústria de beneficiamento de batatas utilizando Cyprinus carpio como bioindicador - Baggiotto, Carine (2017)
When released into water bodies, the effluent from the potato processing industry can cause serious damage to aquatic biota, causing even death of fish through intoxication. Fish have been widely used in ecotoxicological studies over the years. The objective of this work was to evaluate the possible effluent toxicity from the potato processing industry through of biochemical biomarkers using fish as bioindicators. Sixty carp (Cyprinus carpio) were used to evaluate the oxidative damages caused by the potato processing industry effluent, as well as the fish antioxidant defense system. The effluent was collected in a sedimentation tank from potato processing industries (Solanum tuberosum) in Silveira Martins-RS. Physical and chemical analyzes and pesticides concentrations were carried out in the effluent, as well as a critical legislation analysis. The fish were exposed to the gross effluent and collected after 7, 14 and 28 days. Brain, gills, liver and muscle were used to biochemical analysis. Acetylcholinesterase, Catalase and Superoxide Dismutase activity, as well as the determination of Thiobarbituric Acid Reactive Substances (TBARS) were evaluated. Seven pesticides were found in the effluent, and the physicochemical analyzes showed that turbidity and suspended solids are in disagreement with the legislation. TBARS levels were increased in fish liver after 7 and 14 days, in gills increased after 7 days. AChE activity was not altered in brain, but in muscle after 7, 14 and 28 days an increased were observed. The SOD activity did not present alteration in liver in any period tested. CAT activity in gills increased after 7 and 14 days, whereas no changes were observed in liver. The results suggest that the effluent can cause oxidative stress, affecting the biochemical and enzymatic parameters in carps and the pesticide residues analysis should be required in the legislation, because only with the analyzes currently required, it is not possible to measure all the substances that are being released into the water bodies.